Investments : principles and concepts - Jones, Charles P. (Asia : John Wiley & Son, Inc., 2010)
Throughout changing investment opportunities, problems, and controversies, Charles P. Jones s Investments remains one of the most readable and comprehensive investments texts today.
Chapter 1 Investing is an Important Activity Worldwide -- Chapter 2 Investment Alternatives: Generic Principles All Investors Must Know -- Chapter 3 Indirect Investing: A Global Activity -- Chapter 4 Securities Markets Matter to All Investors -- Chapter 5 All Financial Markets Have Regulations and Trading Practices -- Chapter 6 Return and Risk: The Foundation of Investing Worldwide -- Chapter 7 Portfolio Theory is Universal -- Chapter 8 Portfolio Selection for All Investors -- Chapter 9 Asset Pricing Principles -- Chapter 10 Common Stock Valuation Lessons for All Investors -- Chapter 11 Managing a Stock Portfolio: A Worldwide Issue -- Chapter 12 What Happens If Markets Are Efficient Or Not? -- Chapter 13 Economy/Market Analysis Must Be Considered By All Investors -- Chapter 14 Sector/Industry Analysis -- Chapter 15 Company Analysis -- Chapter 16 Technical Analysis -- Chapter 17 Fixed Income Securities Are Available Worldwide -- Chapter 18 Managing Bond Portfolios: Some Issues Affect All Investors -- Chapter 19 Understanding Derivative Securities: Options -- Chapter 20 Understanding Derivative Securities: Futures -- Chapter 21 All Investors Must Consider Portfolio Management -- Chapter 22 Evaluation of Investment Performance: A Global Concept .
Includes index.
Keywords: BUSINESS ENTERPRISE